MANAGING ORGANISATIONAL CONFLICTS WITH EMOTIONAL INTELLIGENCE - Michael Aswin Winardi; Antonius Adi; Budi Riyanto (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Employee well-being is critical within an organisation. Well-being can have a wide range of effects on employees and organisations, including quality, standards, and sustainability. The COVID-19 pandemic has had a negative influence on worldwide economy, particularly on the service sector. Many service businesses have battled with managing their service ecosystems and operational differences. These conditions have had an impact on service employees' well-being. Internal conflict is unavoidable and can have an impact on organisational effectiveness. Socio-emotional competency, such as effective conflict resolution procedures, is required to successfully manage difficult client interactions. The goal of resolving conflict in the service business is to reduce negative consequences and enhance positive ones, resulting in improved learning within the company. Individuals with strong emotional intelligence (EI) can regulate their emotions in interpersonal and organisational situations. The study uses a quantitative approach to collect data (a questionnaire survey) from targeted respondents in the hotel business. This study is based on two ideas: conflict and affect event theories. This study examines the relationship between emotional intelligence, organisational conflict, and employee well-being, with an emphasis on hotel staff.